THE INFLUENCE OF TRAINING AND DEVELOPMENT, TALENT MANAGEMENT, REWARDS AND APPRECIATION IN IMPROVING EMPLOYEE PERFORMANCE AT AIRNAV INDONESIA DENPASAR BRANCH, BALI - Ni Nyoman Astri Pratiwi; Putu Indah Rahmawati; Made Ary Meitriana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to see the influence of training and development, talent management, rewards and appreciation in improving employee performance at Airnav Indonesia Denpasar Branch, Bali. This study uses a quantitative approach, using regression analysis to see how these variables relate. The results show that training and development do not have a positive effect on employee performance, talent management provides an important contribution in ensuring that employees with the best potential are placed in the right positions, rewards and appreciation have a significant effect on increasing employee motivation and job satisfaction and training and development, talent management, and rewards and appreciation simultaneously have a direct influence on employee performance.